2013
DOI: 10.1183/09031936.00137612
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bronchiectasis and trapped air on quality of life and exacerbations in cystic fibrosis

Abstract: Cystic fibrosis (CF) is primarily characterised by bronchiectasis and trapped air on chest computed tomography (CT). The revised Cystic Fibrosis Questionnaire respiratory symptoms scale (CFQ-R RSS) measures health-related quality of life.To validate bronchiectasis, trapped air and CFQ-R RSS as outcome measures, we investigated correlations and predictive values for pulmonary exacerbations. CF patients (aged 6-20 years) underwent CT, CFQ-R RSS and 1-year follow-up. Bronchiectasis and trapped air were scored usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 29 publications
7
37
0
2
Order By: Relevance
“…Another limitation of the CD203c BAT is that it may be difficult to discriminate patients sensitised to A. fumigatus from patients with CF-ABPA, but we believe additional analysis of A. fumigatus-specific IgE levels may be able to resolve this issue in most cases [22]. Finally, it has been shown that HRCT can detect pulmonary exacerbations in CF patients [37]. As we did not design our study to compare BAT CD203c levels in patients with CF and ABPA to chest HRCT bronchiectasis scores, future long-term studies will be necessary to assess the potential correlation between the persistence of basophil CD203c activation in patients with CF-ABPA and progression of bronchiectasis on chest HRCT.…”
Section: Discussionmentioning
confidence: 98%
“…Another limitation of the CD203c BAT is that it may be difficult to discriminate patients sensitised to A. fumigatus from patients with CF-ABPA, but we believe additional analysis of A. fumigatus-specific IgE levels may be able to resolve this issue in most cases [22]. Finally, it has been shown that HRCT can detect pulmonary exacerbations in CF patients [37]. As we did not design our study to compare BAT CD203c levels in patients with CF and ABPA to chest HRCT bronchiectasis scores, future long-term studies will be necessary to assess the potential correlation between the persistence of basophil CD203c activation in patients with CF-ABPA and progression of bronchiectasis on chest HRCT.…”
Section: Discussionmentioning
confidence: 98%
“…Using chest CT as the reference test, a cut-off value of 26 % or higher, representing severe bronchiectasis, was defined as a true-positive finding for the MRI-bronchiectasis subscore; 26 % represents the percentage of the maximum possible score for bronchiectasis, which is 12 per each lobe and 72 in total according to CF-CT. This cut-off of 26 % was based on the median value of bronchiectasis severity observed in two cohort studies, with either mild or severe CF lung disease [3,22], using receiveroperating characteristic analysis to determine different cut-off values. Sensitivity, specificity, PPV and NPV were calculated for each observer (obs 1 and obs 2 ), in addition to the mean of the bronchiectasis scores of both observers (mean obs 1+2 ).…”
Section: Sensitivity Specificity Ppv and Npv Of Mri Versus Ctmentioning
confidence: 99%
“…Life expectancy is reduced because of progressive lung disease, characterised by several structural lung changes, most importantly bronchiectasis and trapped air [2,3]. To guide therapy to prevent or reduce bronchiectasis and trapped air, it is crucial to monitor CF lung disease at regular intervals.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the existence of air trapping in infants with CF is predictive of future pulmonary exacerbations (41) and is a risk factor for bronchiectasis (28). In newborn piglets with CF, air trapping cannot be attributed to mucus plugging, infection, inflammation, or their secondary consequences, because these changes are not present (10,12,15).…”
Section: Air Trapping Occurs In the Absence Of Infection Or Inflammatmentioning
confidence: 99%